Cellular Membrane Composition Requirement by Antimicrobial and Anticancer Peptide GA-K4 - Mishig-Ochir, Tsogbadrakh; Gombosuren, Davaadulam; Jigjid, Altanchimeg; Tuguldur, Badamkhatan; Chuluunbaatar, Galbadrakh; Urnukhsaikhan, Enerelt; Pathak, Chinar; Lee, Bong-Jin (Protein and Peptide Letters, 2017)
Naturally occurring antimicrobial peptides important for innate immunity are widely studied for their antimicrobial and anticancer activity. The primary target of these AMPs is believed to be the bacterial cytoplasmic membrane. However, the interaction between cytoplasmic membrane and the antimicrobial peptides remains poorly understood. Therefore to focus on the target membrane composition that is required by AMPs to interact with membranes, we have examined the interaction of the antimicrobial and anticancer active 11-residue GA-K4 (FLKWLFKWAKK) peptide with model and intact cell membranes. Effect on the structural conformational properties of GA-K4 peptide was investigated by means of far-UV CD and fluorescence spectroscopic methods. The different conformation of GA-K4 peptide in large unilamellar vesicles (LUV) bilayer and micelle environment suggest that the curvature has an influence on the secondary structure acquired by the peptide. Furthermore, the leakage experiment result confirmed that GA-K4 induced the leakage of cytoplasmic membrane in Staphylococcus аureus bacterial cells. Fluorescence data revealed the interfacial location of GA-K4 peptide in the model membranes. The blue-shift in emission wavelength by tryptophan residues in fluorescence data indicated the penetration of GA-K4 peptide in micelles and phospholipid bilayers. These results showed that the GA-K4 peptide is a membrane-active peptide and its activity depends on membrane curvature and lipid composition. Although further studies are required to confirm the mechanism of action, the data suggest mechanism of toroidal pore formation for the interaction of GA-K4 peptide with membranes. Our studies will be helpful in better understanding of the membrane requirment of peptides to express their therapeutic effects.
Keywords: model membranes